Implementasi Algoritma Golmb Code Dalam Kompresi File Video - Setia Nengsih Ritonga (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Video files are one type of digital file that is widely used by the public, in video files there is a lot of information because they have more capacity for storage. Information exchange in today's technological era is very sophisticated, only relying on an internet connection, files can be sent quickly and easily to the recipient, the delivery speed process depends on the size of the file and the strength of the internet used, the more information in it, the slower the delivery. Sending large files will require a lot of storage and can affect the overall content of the information not being conveyed and there will be rejection from the recipient. The solution to this problem is to do file compression. In this study the author will discuss the method with the Golomb code algorithm in video file compression. Analysis of the performance of this algorithm with the aim of knowing its performance against video files with the .mp4 extension. In this algorithm there are two stages, namely compression and decompression, the compression stage with the aim of compressing the file size so as to speed up the sending process and the decompression stage aiming to return the file size to its original (original) size. The results of the application that the author did manually with the Golomb code algorithm were based on the values of several elements such as the Ratio of Compression (RC), Compression Ratio (CR), Redundancy (Rd), Space Saving (SS), Bitrate, and Time Compression (TC). , with the conclusion that the percentage of video file compression results using the golomb code algorithm was declared successful.